ANALYSING CONVENTIONAL DETERRENCE IN A NUCLEARISED SOUTH ASIA - Nasir Mehmood; Syeda Zainab Asif (Margalla Papers)
This article advances the debate on the dynamics and effectiveness of conventional deterrence in a nuclearised South Asia. Conventional deterrence is primarily based on the precept of dissuasion, playing an integral part in states’ defence policies. It leverages conventional military capabilities and the adept use of military strategy to dissuade opponents from initiating major campaigns and escalations into full-blown war. The study validates the role of conventional deterrence by carefully examining two India-Pakistan sub-cases: the 1999 Limited Kargil War and the 2019 Balakot Aerial Confrontation. Through these two sub-cases, the research elucidates the complex relationship between numerical strength and intelligent military planning in denying opponents their military objectives and preventing the employment of nuclear weapons.